The Elementary Graders' Description of Their Ability to Write Analytical Exposition Text - Afore Tahir Harefa; Elwin Piarawan Zebua (Universitas Nias, 2023)
Writing is the process of putting thoughts into words on a piece of paper and presenting them to the reader. A spoken or written text that aims to persuade the audience or readers of something—either pro or con, depending on the situation—is an analytical exposition text. The purpose of the research was to describe the students' writing abilities and the factors that affect them in order to understand their capacity for producing analytical exposition texts. Using a Hymp-Lyons scoring rubric, which includes Thesis Statement, Arguments, and Reiterations, the students' performance on the test was evaluated.The research employed a descriptive qualitative methodology. Following Gay et al.'s recommendations for reading and taking notes, characterizing the environment, and categorizing research data, the analysis of the data was carried out in this manner. The class XI-MIPA students, which had 20 students, served as the research's informants. Data has been collected through student workbooks and interviews with English teachers and students.After conducting the analysis of students’ analytical exposition text, the result showed that 14 students (70%) were able to write an analytical exposition text, and only 6 students (30%) were not able to write an analytical exposition text. After conducting the analysis of students’ answer in interview sheets, the result showed that a lot of different factors affected the result of their writing. In the final analysis, the majority of XI-MIPA students were able to write analytical exposition texts with a solid generic structure due to a number of key factors, including their background knowledge of the subject, the depth of their understanding of analytical exposition texts, and how well they applied the writing process in their work.